(untitled) (VERITAS LEGIS JOURNAL, 2026)
The article examines the current state and development trends of the institution of parole (early conditional release) in the Republic of Kazakhstan within the context of criminal policy. The author emphasizes that parole is an important element of the legal mechanism for the rehabilitation of convicts, performing resocialization, economic, and humanitarian functions. The relevance of the study is determined both by changes in legislation and by the need to ensure compliance with constitutional principles when introducing restrictions on the application of parole. The purpose of the study is to analyze the legal foundations of parole, identify existing restrictions on its application, and assess their compliance with the Constitution of the Republic of Kazakhstan. The tasks also include examining judicial practice and analyzing the legal positions of the Constitutional Court that influence the application of the institution of parole. The study found that Kazakhstan’s state policy demonstrates a tendency toward tightening the conditions for parole for certain categories of crimes, primarily corruption-related offenses and crimes against the sexual inviolability of minors. The analyzed regulatory rulings of the Constitutional Court reveal issues of inconsistency in law enforcement, particularly in interpreting provisions on the retroactive effect of the law and the correlation between the norms of the Criminal Code and the Criminal Executive Code. In conclusion, the article highlights the need to improve parole legislation and ensure uniform judicial practice, which will strengthen legal certainty and help achieve a balance between justice, humanism, and public safety. The author concludes that constitutional oversight plays a key role in aligning parole restrictions with the principles of proportionality and the inadmissibility of unjustified deterioration of the situation of convicts.